Tutorial on Computer Organization and Architecture-Advantages and Challenges - Hiremath, Namrata D.; Umadevi, F. M.; Meena, S. M. (Journal of Engineering Education Transformations, 2018)
Teaching Computer Organization and Architecture to the students of Computer Science and Engineering is a responsible task, as this course lays foundation for various other courses like System Software, Principles of Compiler design and Operating System. But it’s always been a challenge for the course instructor to teach the course effectively. The students of Computer Science and Engineering have been inclined towards software courses and hence teaching a course without associated laboratory, has been a drawback. To aid students with better understanding of concepts, course instructors decided to redesign the course. The tutorial was planned to address the previously mentioned challenges. The most popular RISC ARM processor was chosen as a case study. To measure the effectiveness of the tutorial, activities were conducted and evaluated as per designed rubrics. In this paper we highlight the challenges and the advantages of tutorial. As a result, we have noticed that students have shown better understanding of the courses.